An assessment in supporting online distance learning by the librarians of selected schools in Metro Manila - Bolos, Veronica A. (Animo Repository, 2020)
Online distance learning has many definitions such as e-learning, web-based learning, virtual learning, distance learning, and blended learning. The growth of online learning is supported and delivered through the use of computer networks such as internet and it shows challenges for library services. This study assessed the readiness of librarians in supporting online distance learning of of selected libraries in Metro Manila. This study used descriptive survey method and data were gathered through a research-made questionnaire that were taken from several concepts and research literature reviewed by the researcher. From the findings of this study, it is concluded that librarians from selected libraries in Metro Manila were ready to support online library services to their patrons. However, it is recommended that they attend more training and/or seminars on how to deliver and enhance their online library services to their community.